2020
DOI: 10.3390/microorganisms8121964
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Colistin and Azidothymidine Demonstrates Synergistic Activity against Colistin-Resistant, Carbapenem-Resistant Klebsiella pneumoniae

Abstract: Carbapenem-resistant Enterobacteriaceae (CRE) is listed as an urgent threat by the World Health Organization because of the limited therapeutic options, rapid evolution of resistance mechanisms, and worldwide dissemination. Colistin is a common backbone agent among the “last-resort” antibiotics for CRE; however, its emerging resistance among CRE has taken the present dilemma to the next level. Azidothymidine (AZT), a thymidine analog used to treat human immunodeficiency virus/acquired immunodeficiency syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The checkerboard analysis revealed 60.9% (14/23), 87.1% (27/31), 100% (7/7), and 92.31% (12/13) synergetic effects in ESBL-producing E. coli, ESBL K. pneumoniae, NDM-1-producing strains, and mcr-1-positive E. coli, respectively. In another evaluation conducted in Taiwan, Chang et al reported 100% synergistic activities for both KPC-producing and non-KPC-producing colistin-resistant CRKP isolates [12]. In vivo results demonstrated an extended lifespan and decreased risk ratios in a Caenorhabditis elegans model infected by a KPC-producing colistin-resistant CRKP isolate, positive support that AZTcolistin possessed the potential for treating CRKP infections.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The checkerboard analysis revealed 60.9% (14/23), 87.1% (27/31), 100% (7/7), and 92.31% (12/13) synergetic effects in ESBL-producing E. coli, ESBL K. pneumoniae, NDM-1-producing strains, and mcr-1-positive E. coli, respectively. In another evaluation conducted in Taiwan, Chang et al reported 100% synergistic activities for both KPC-producing and non-KPC-producing colistin-resistant CRKP isolates [12]. In vivo results demonstrated an extended lifespan and decreased risk ratios in a Caenorhabditis elegans model infected by a KPC-producing colistin-resistant CRKP isolate, positive support that AZTcolistin possessed the potential for treating CRKP infections.…”
Section: Discussionmentioning
confidence: 92%
“…To this end, some β-lactam-βlactamase inhibitor combination therapies were introduced into clinical settings recently, such as meropenem-vaborbactam, imipenem-relebactam, and ceftazidime-avibactam [7][8][9][10]. Moreover, combinations of azidothymidine (AZT), an antiviral agent usually used against HIV infection, plus other agents, were also reported, including AZT-colistin and AZTfosfomycin [11][12][13]. Hu et al obtained 74 antibiotic-resistant Enterobacteriaceae strains from hospitals in 9 countries, including 23 ESBL-producing E. coli, 31 ESBL, 7 NDM-1-producing strains, and 13 mcr-1-positive E. coli [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Azidothymidine is an approved antiretroviral drug, and it also exhibits antibacterial activities against Enterobacteriaceae by acting on bacterial DNA synthesis (32). Previous studies demonstrated significant synergistic activities of azidothymidine for retaining therapeutic efficacies of colistin in colistin-resistant K. pneumoniae that express mcr-1, both in vitro and in vivo (33,34).…”
Section: Non-antibiotic Drugs In Combination Therapies To Overcome Colistin-resistant K Pneumoniae Associated With Utimentioning
confidence: 99%